Vendor selection for an autobot system for VDK gloves manufacturing company using Fuzzy Analytical Hierarchy Process - Kumar, Vignesh Devar; Kashim, Rosmaini; Mat Desa, Wan Laailatul Hanim; Mat Rani, Ruzanita; Guhamani, Ravikumar (UUM Press, 2022)
Vendor selection of an autobot system is not a simple process as it typically involves multiple criteria, and it needs human judgement. Therefore, there is a requirement to have a better system for vendor selection due to ambiguity and vagueness that exist in dealing with multiple criteria decision making (MCDM) problems. In this study, there are two main objectives which is to identify the important criteria for vendor selection and to determine the most preferable vendor based on selected criteria using Fuzzy Analytical Hierarchy Process (FAHP) for the VDK gloves manufacturing company. The finding shows seven criteria which are flexibility, reputation, service, price, quality, distance, and competitiveness chosen by the experts. Based on FAHP, Vendor 1 is selected as the most preferable vendor with the score of 0.4708 since it met all the criteria chosen by the VDK glove manufacturing company’s expertise. As a recommendation this method can also be adopted by the company to manage other selection problems.